2022
DOI: 10.1002/viw.20220004
|View full text |Cite
|
Sign up to set email alerts
|

Nanoantidote for repression of acidosis pH promoting COVID‐19 infection

Abstract: Acidosis, such as respiratory acidosis and metabolic acidosis, can be induced by coronavirus disease 2019 (COVID‐19) infection and is associated with increased mortality in critically ill COVID‐19 patients. It remains unclear whether acidosis further promotes SARS‐CoV‐2 infection in patients, making virus removal difficult. For antacid therapy, sodium bicarbonate poses great risks caused by sodium overload, bicarbonate side effects, and hypocalcemia. Therefore, new antacid antidote is urgently needed. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…In our study, these data are reinforced by the fact that the estimated glomerular filtration rate is also among the most relevant parameters, as it has been shown in other studies to be a good predictor of admission mortality in COVID-19. In addition, our study showed a high relevance of FiO2, closely related to acute hypoxic respiratory failure-, and potassium and pH as predictors of a poor outcome and mortality, which is compatible with the results obtained by Satici et al [48], Noori et al [49], or Liu et al [50]. Interestingly, hypokalemia has also been shown to be an indicator of a poorer prognosis and longer days of negative nucleic acid conversion.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, these data are reinforced by the fact that the estimated glomerular filtration rate is also among the most relevant parameters, as it has been shown in other studies to be a good predictor of admission mortality in COVID-19. In addition, our study showed a high relevance of FiO2, closely related to acute hypoxic respiratory failure-, and potassium and pH as predictors of a poor outcome and mortality, which is compatible with the results obtained by Satici et al [48], Noori et al [49], or Liu et al [50]. Interestingly, hypokalemia has also been shown to be an indicator of a poorer prognosis and longer days of negative nucleic acid conversion.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, COVID-19 promotes respiratory acidosis among critically ill patients [27]. As a way to quickly reverse acute acidemia, the previous pole of therapy placed great assertiveness on intravenous sodium bicarbonate, which significantly reduces the primary composite outcome and mortality in patients with acute kidney injury [28]. We observed a decrease in pH in elderly patients with type 2 diabetes, which was reversed following complete remission from COVID-19.…”
Section: Discussionmentioning
confidence: 73%
“…In parallel, acidosis enhances COVID-19 infection by increasing cell membrane ACE2 expression. Therefore, acidosis promotes further infection and difficulty in recovery from COVID-19 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of MNP: First, the poly(ethylene glycol)-poly(glutamic acid) (PEG-P(Glu)) block copolymer was synthesized and obtained using Fuchs-Farthing reaction as previously reported. [22] 1 H-NMR hydrogen spectrum (300 MHz; solvent: D 2 O) was used to determine the substitution ratio of P(Glu). Then, 1 mL Tris-HCl buffer (10 mm, pH 7.6) containing 10 mg CaCl 2 , 3 μg TGF-𝛽, 300 μg CAT, 10 mg mPEG-P(Glu) polymer.…”
Section: Methodsmentioning
confidence: 99%